DIFFICULTY INDEX, DISCRIMINATION INDEX, SENSITIVITY AND SPECIFICITY OF SINGLE BEST ANSWER QUESTIONS TO ASSESS MEDICAL STUDENTS’ PERFORMANCE IN SEND UP EXAMINATION AT LAHORE MEDICAL & DENTAL COLLEGE - Zafar, Uzma; Ali, Zaima; Khalid, Attiqa; Zaki, Saima; Naeem, Faiqa Jabeen; Chaudhry, Muhammad Asad (Pakistan Journal of Physiology, 2022)
Background: Item analysis of the single best answer question based assessment is a simple and valuable method that can help the examiners to check the reliability and validity of this examination tool. This study aimed to determine difficulty index and discrimination index of single best answer question (SBAQ) based send-up Physiology paper of 1st Prof MBBS, and to check sensitivity and specificity of SBAQs to predict undergraduate medical students’ performance. Methods: This was an observational study. A retrospective review of undergraduates’ examination performance was done after approval from Institutional Review Board. Theory paper consisted of 45 SBAQs. Each SBAQ comprised a stem followed by five options. One option was correct and rest four were distractors. Data was analysed on SPSS-22. Difficulty and discriminative index was calculated. Receiver operating characteristics (ROC) curve was generated. The sensitivity and specificity of SBAQ was determined. Results: Out of 45 items, 33 (73%) were having difficulty index within the acceptable range (30–70%), 3 (6.7%) were very easy with the difficulty index of more than 70%, and 9 (20%) very difficult with the index of less than 30%. Mean±SD difficulty index was 47.45±17.83. Discrimination index revealed 33 items within acceptable range, 10 were poor and 2 items revealed negative scoring. Mean±SD discrimination index was 0.30±0.19. ROC curve revealed AUC of 0.86 (p=0.000; CI= 0.803-0.90) with sensitivity of 84% and specificity of 89%. Conclusion: Mean difficulty index of send-up paper was within acceptable limits. However, discrimination index identified 12 items that need revision. Pak J Physiol 2022;18(3):44?7